Acute Urticaria in Inpatients Undergoing Non-emergent Coronary Angiography With Corticosteroid Prophylaxis: A Retrospective Study - Bangtao Chen; Fubing Yu; WenChieh Chen; Yong Wang; Fei Hao (Frontiers in Medicine, 2021)
Background and Aims: Acute urticaria (AU) is the most frequently reported immediate hypersensitivity reaction in skin by administration of iodinated contrast media (ICM). We aimed to establish the pattern and identify the risk factors of AU among inpatients undergoing non-emergent coronary angiography (CAG) with prophylactic corticosteroids in China.Methods: Medical records of 19,326 adult inpatients undergoing non-emergent CAG with prophylactic methylprednisolone in 2013–2019 were retrospectively investigated. AU was identified within 1 h post-ICM administration, and diffuse involvement was defined when wheals occur in two or more body parts, including the back, abdomen, chest, and extremities. Age- and sex-matched inpatients (1:4) without AU were randomly selected for assessment of risk factors.Results: Approximately 0.8% of CAG inpatients had AU, including 101 diffuse and 64 limited form. The diffuse AU was more common in settings of non-diagnostic CAG, iohexol used, average ICM injection≥3 ml/min, recurrent CAG, and past history of immediate hypersensitivity to ICM. Inpatients with preexisting allergies, decreased evaluated glomerular filtration rate, and increased high sensitivity C reactive protein or neutrophil-to-lymphocyte ratio prior to CAG had a higher probability of AU (odds ratio >1, P < 0.05 for all variables). All AU inpatients complained of pruritus, and mild itching predominated. AU dissipated in several days under treatment of ebastine or levocetirizine 10 mg/daily, but ebastine showed superiority.Conclusions: ICM-induced AU is not uncommon in non-emergent CAG inpatients with prophylactic methylprednisolone. Preexisting allergies, renal dysfunction, and mild inflammation are high-risk factors, and antihistamine monotherapy is a favorable candidate for ICM-related AU.